The role of colchicine on ventricular remodelling following myocardial infarction and ischemia-reperfusion injury: article review - Caesario, Fahreza; Prasetya, Indra (Heart Science Journal, 2024)
Acute myocardial infarction (AMI) is a major cause of cardiac dysfunction, arrhythmias, and a poor prognosis. Even though new technologies have been developed to aid in opening the culprit coronary artery and correcting ischemia-related stenosis by percutaneous coronary intervention (PCI), the ventricular remodelling that induces cardiac failure as a consequence of AMI remains unchanged. Colchicine, a versatile anti-inflammatory medication, has been documented in mitigating cardiac remodelling and enhancing cardiac function following AMI. This article provides an in-depth review of the processes by which colchicine affects ventricular remodeling after AMI, highlighting the potential role of inflammation in the pathogenesis and progression of ventricular dysfunction.